Measuring Global Poverty: Why PPP Methods Matter - Ackland, Robert; Dowrick, Steve; Freyens, Benoit (The Review of Economics and Statistics, 2013)
We present theory and evidence to suggest that, in the context of analyzing global poverty, the EKS approach to estimating purchasing power parities yields more appropriate international comparison of real incomes than the Geary-Khamis approach. Our analysis of the 1996 and 2005 International Comparison Project data confirms that the Geary-Khamis approach substantially overstates the relative incomes of the world's poorest nations, and this leads to misleading comparisons of poverty across regions and over time. The EKS index of real income is much closer to being a true index of economic welfare and is therefore preferred for assessment of global poverty.